Prophylactic vaccinations management in patients undergoing allergen immunotherapy – a review - Czerwińska, Ewa; Nittner-Marszalska, Marita; Mastalerz-Migas, Agnieszka; Szenborn, Leszek (Family Medicine & Primary Care Review, 2022)
Allergen immunotherapy (AIT) is the only casual method of allergy treatment. It is based on regular administration of a gradually increasing dose of an allergen to induce immunological tolerance to a particular sensitising factor. Due to proven efficacy, including preventive effect as well as favourable safety profile, it should be widely applicable, particularly among older children and adolescents. While the number of patients suffering from non-communicable diseases, including allergies, is rising, there is a false impression that the impact of infectious diseases can be disregarded. Thanks to prophylactic vaccines, many infectious diseases that used to be a threat to people’s lives have been forgotten. In order to tackle familiar and emerging infectious diseases (such as COVID-19), there is a need to keep in mind vaccinations in all age groups. As allergen immunotherapy and prophylactic vaccines affect the immunologic system, performing both interventions in one patient may raise concerns about safety and effectiveness. However, a large-scale study on this topic has not been performed to date. This article summarises immunological responses occurring after contact with pathogens and allergens as well as describes reactions triggered by prophylactic vaccines and AIT. What is more, possible interference of receiving both a prophylactic vaccine and AIT is discussed.